Successful management of vulvar proximal-type epithelioid sarcoma in pregnancy - Yuji Orita; Masaki Kamio; Akio Tokudome; Ikumi Kitazono; Fumino Ichihara; Hiroaki Kobayashi (Elsevier, 2022)
Vulvar proximal-type epithelioid sarcoma during pregnancy is extremely rare; only two reports are available to date. Herein, we describe a 36-year-old woman who presented with a pigeon-egg-sized solid mass with cystic component on the left labia majora at 18 weeks of gestation. The patient underwent tumor resection at 23 weeks of gestation and was diagnosed with epithelioid sarcoma, proximal-type. At 29 weeks of gestation, elective cesarean section, radical local resection of the vulva and vagina, and inguinal lymphadenectomy were performed. After surgery, she underwent six courses of adjuvant chemotherapy (doxorubicin 60 mg/m2 and cisplatin 50 mg/m2) every four weeks. The patient and her baby survived with neither recurrence nor complications until 5 years. Aggressive management for proximal-type epithelioid sarcoma, such as early termination of pregnancy and operation, can improve maternal outcomes.